2012
DOI: 10.1007/978-1-4614-4989-8_15
|View full text |Cite|
|
Sign up to set email alerts
|

Oscillations in Cerebral Haemodynamics in Patients with Falciparum Malaria

Abstract: Spontaneous oscillations in cerebral haemodynamics studied with near-infrared spectroscopy (NIRS), become impaired in several pathological conditions. We assessed the spectral characteristics of these oscillations in 20 patients with falciparum malaria admitted to Ispat General Hospital, Rourkela, India. Monitoring included continuous frontal lobe NIRS recordings within 24 h of admission (Day 0), together with single measurements of a number of clinical and chemical markers recorded on admission. Seven patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
(25 reference statements)
0
13
1
Order By: Relevance
“…Because of these modulation patterns, we are convinced that we measured physiological oscillations rather than non‐biological artefacts or systematic noise. In fact, different patterns of changing hemodynamic oscillations measured with NIRS have been widely reported by numerous studies from different groups in a vast population, including different species, healthy young and elderly populations, and patients with various pathological diseases (Obrig et al ., ; Schmidt‐Lucke et al ., ; Schroeter et al ., , ; Li et al ., , , ; Nasi et al ., ; van Beek et al ., ; Sassaroli et al ., ; Kolyva et al ., ; Cui et al ., ; Vermeij et al ., ). Our recent study showed that the cerebral hemodynamic oscillations in endothelial and neurogenic ranges measured with NIRS were enlarged by apnea events in patients with sleep apnea syndrome (SAS), and the increased oscillations induced by apnea events can be restored under positive airways pressure therapy (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these modulation patterns, we are convinced that we measured physiological oscillations rather than non‐biological artefacts or systematic noise. In fact, different patterns of changing hemodynamic oscillations measured with NIRS have been widely reported by numerous studies from different groups in a vast population, including different species, healthy young and elderly populations, and patients with various pathological diseases (Obrig et al ., ; Schmidt‐Lucke et al ., ; Schroeter et al ., , ; Li et al ., , , ; Nasi et al ., ; van Beek et al ., ; Sassaroli et al ., ; Kolyva et al ., ; Cui et al ., ; Vermeij et al ., ). Our recent study showed that the cerebral hemodynamic oscillations in endothelial and neurogenic ranges measured with NIRS were enlarged by apnea events in patients with sleep apnea syndrome (SAS), and the increased oscillations induced by apnea events can be restored under positive airways pressure therapy (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed on oscillations of HbO 2 , because spontaneous oscillations are most prominent in HbO 2 (Obrig et al ., ; Schroeter et al ., ; Li et al ., ; Kolyva et al ., ). In order to make valid comparisons of SDs and PSDs of different vasomotion components between different sleep stages, the SDs and PSDs of cerebral and muscular HbO 2 and SpO 2 were normalized to their mean values of the whole‐night measurements (Schroeter et al ., , ; Kolyva et al ., ). For example, normalization of the SDs of cerebral HbO 2 during LS was performed with the formula normalized‐SD LS = 3 × SD LS /(SD LS + SD SWS + SD REM ), where SD LS , SD SWS and SD REM were the SDs of cerebral HbO 2 during LS, SWS, and REM, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…These large oscillations, with amplitudes comparable to the hemodynamic response to sensory stimulus, are sporadic, but have been shown to occur in the rat (Golanov et al, 1994; Grosberg et al, 2012; Majeed et al, 2009; Mayhew et al, 1996; Saka et al, 2010), cat (Spitzer et al, 2001), awake rabbit (Hundley et al, 1988) and non-invasively in humans using near-infrared spectroscopy (Elwell et al, 1999; Kolyva et al, 2013; Näsi et al, 2011; Obrig et al, 2000; Sassaroli et al, 2012; Schroeter et al, 2005), and fMRI BOLD (Mitra et al, 1997). In some cases the appearance of SSHOs in the brain has been linked to distinct physiological conditions or states of arousal (Näsi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] The spontaneous low frequency oscillation (4-150 MHz) in these hemodynamic parameters further re°ects vasomotion in cerebral tissue. 16,[36][37][38] As a totally non-invasive and non-radioactive optical method, NIRS has sub-second temporal resolution and less motion restriction, 39,40 making it a powerful tool for all night sleep study. Although several studies with NIRS repeatedly reported an impairment of cerebral oxygenation in the patients with sleep apnea, [41][42][43][44][45] we still lack knowledge about the changes of cerebral autoregulation mechanism under CPAP therapy.…”
Section: Introductionmentioning
confidence: 99%